Digital innovation in the supply chain management - Nowicka, Katarzyna (Cyfrowe innowacje w zarządzaniu łańcuchem dostaw, 2019)
Digital innovations result from the implemented digital technologies and a combination of their properties. They can form the basis for building digital supply chains (networks) that are a new stage in their evolution. The article explains the concept of digital innovation and highlights the place of technology in supply chain management. The goal of the article is to present the results of research carried out using the CATI method among supply chain managers using digital technologies. The most important changes resulting from the application of these technologies include not only the increase in the level of process automation, but also the extension of distribution with a new sales channel, as well as the possibility of simultaneous communication with several partners and access to information related to logistics activities, i.e. free space in warehouses and planned freight routes. Such effects give the potential to improve the competitive position and constitute a premise for the further development of the digital transformation of supply chains. In this process, however, not only are the costs of the implemented technologies important (indicated as the main barrier to their implementation), but also the competences enabling the identification of digital innovations that best respond to the needs of supply chain management
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 202-214
Keywords: digital innovation; digital supply chain; digital transformation of supply chains; innowacje cyfrowe; cyfrowy łańcuch dostaw; cyfrowa transformacja łańcuchów dostaw